Avaliação da influência do discurso ambiental curricular das comunidades locais do Distrito de Dondo-Moçambique- - Mulhaisse, Raimundo Alberto (2006)
The present research evaluates lhe influence that lhe enviornrnental speech syllabus exercises on environrnental speech of local communities in Dondo District, in other words, it studies lhe interference that lhe environrnental speech of local commuinities undergoes in school environrnental speech. The study starts with a theoretical revision in arder to build lhe contextual frame of environrnental education, on which it analises lhe integral fonnation of the citizen, focuses on a brief history of environrnental education and analises lhe ways of its accomplishment, institutionalisation, necessity of aquiring the knowledge and teacher trainning taking into account lhe inviornrnental education. The methodologic approach is based 00 qualitative reserch and trom this poiot a case study is developed. The selected teaching institutions for the case study were Dondo Secondary school and Mafambisse Secondary School, in Dondo District, Sofala Privince in Mozambique. These are two schools with sem i-rural caracteristics and it is only in these two schools where students attended lhe fIrst cycle, that is, trom grade 8 to grade 10 of lhe general secondary education in Dondo District, till lhe 2005 academic real. The research results show that the environrnental speech syllabus is not clearly reflected on teachers speech Dor on student's parents and this last speech reflects the way how local communities are organised and deal with nature. The students' environrnental speech reflects lhe teahers' environrnental speech. The teacher trainning with relevant knowledge on environrnental issues appears to be fundamental condition so that lhe environrnental speech syllabus can be reflected on communities' environrnental speech. The research aims to contribute on the improvement of lhe school perfonnance in lhe context of environrnental education of the local communities. A school has to be lhe responsible for lhe education of the individual and consequently of lhe society, since there is transmission of a variety of infonnation and knowledge, this generates dynamic system that covers every one